Dialectologia et Geolinguistica : Journal of the International Society for Dialectology and Geolinguistics (De Gruyter Mouton, 1993)
Dialectologia et Geolinguistica publishes contributions on the variation of languages world-wide, systematic and inherent, diachronic and synchronic, regional and social, based on either oral or written data. It is open to all theoretical and methodological approaches. The journal is the official journal of the International Society for Dialectology and Geolinguistics (ISDG/SIDG).